Evaluation of β2-microglobulin in the condition and prognosis of psoriasis patients - Ling Han; Yixiao Gan; Juan Du; Yao Hu; Yanwen Chen; Qiong Huang; Zhenghua Zhang; Nikhil Yawalkar; Kexiang Yan; Zhicheng Wang (Taylor & Francis Group, 2024)
Background Numerous studies have linked the inflammatory pathway in psoriasis and metabolic disease, while no specific marker defined it. It is worth exploring the association of β2-microglobulin (β2M) in psoriasis severity and comorbidities.Objectives To investigate the correlation between blood β2M level and psoriasis severity, to explore the inflammatory factors influencing the occurrence of psoriasis comorbidities such as arthritis, diabetes, and hypertension.Methods Ninety-seven psoriasis patients were analyzed in the cohort retrospective study during 12 weeks.Results Significantly higher levels of blood β2M and ESR were observed in the group that patients' PASI ≥10 than in the group that PASI <10. Blood β2M level had strong significantly positive correlations with the PASI in Pearson's correlation analysis. In the model that systemic inflammatory factors to find psoriasis comorbidity risk factors, logistic regression analysis showed that blood β2M level was the significant risk factor associated with diabetes and hypertension. High-sensitivity C-reactive protein (hsCRP) was the significant risk factor associated with arthritis.Conclusions Patients with a severer psoriasis tended to have higher blood β2M levels and severer inflammatory state. In the systemic inflammation indexes, the level of blood β2M affected the risk of hypertension and diabetes, and hsCRP affected the risk of arthritis in patients with psoriasis.